A comprehensive review on tribological behaviour of hybrid Nanocellulose-CuO as nanolubricant for piston ring cylinder liner application - Sakinah, Muhamad Hisham; Norazlianie, Sazali; Kadirgama, Kumaran; Ramasamy, Devarajan (Penerbit Akademia Baru, 2024)
Friction coefficient and wear rate are crucial performance for the development of nanolubricants, which are of great significance for realizing energy conservation and prolonging service life of mechanical components. Herein, this review systematically describes the progress on nanocellulose (CNC) and Copper (II) oxide (CuO) as effective nanoparticles for developments of nanolubricant as oil additives for improving the anti-friction and wear resistant for piston ring-cylinder liner contact. Additionally, we point out several problems existing in the applications of CuO and CNC additives propose the possible solutions. Finally, the research prospects of CNC-CuO in the field of tribology are prospected.